2017
DOI: 10.1016/j.eats.2017.05.031
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Treatment of Type 1B Triangular Fibrocartilage Complex Tear by “Outside-In” Repair Technique Using Transcapsular Transverse Mattress Suture

Abstract: Triangular fibrocartilage complex (TFCC) injuries are increasingly recognized as a cause of ulnar-sided wrist pain. Palmer grouped these tears into either traumatic or degenerative, with various subclassifications. Magnetic resonance imaging (MRI), arthrogram, and arthroscopy are the methods used to establish the diagnosis. Several arthroscopic methods of TFCC repair including outside-in, inside-out, and all-inside techniques have been described. The outside-in repair, which involves piercing the TFCC via the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…Scholars have also made some explorations on stitching methods. Bayoumy et al [ 11 ] proposed that the horizontal mattress suture is more biomechanically stable than the longitudinal mattress suture and can effectively reduce the cutting effect of the suture, but it still cannot avoid the complications of the ulnar nerve and the irritation of the knot on the skin. Scholars continue to report that patients who repaired the Palmer I-B TFCC superficial injury via joint capsule suture under arthroscopy were found to have symptoms of nerve irritation after surgery [ 19 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Scholars have also made some explorations on stitching methods. Bayoumy et al [ 11 ] proposed that the horizontal mattress suture is more biomechanically stable than the longitudinal mattress suture and can effectively reduce the cutting effect of the suture, but it still cannot avoid the complications of the ulnar nerve and the irritation of the knot on the skin. Scholars continue to report that patients who repaired the Palmer I-B TFCC superficial injury via joint capsule suture under arthroscopy were found to have symptoms of nerve irritation after surgery [ 19 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, many scholars have reported that patients treated by outside-in suture method have found that the dorsal branch of the ulnar nerve is injured or the local irritation symptoms are found. This is often caused by the suture knot irritating the dorsal branch of the ulnar nerve or the skin [ 2 , 3 , 11 , 17 ]. Our research group innovatively modified the traditional outside-in suture of the joint capsule and modified the traditional extracapsular suture to intracapsular suture and found that the incidence of postoperative nerve irritation in patients can be significantly reduced.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is used to guide the surgical treatment, whether arthroscopic or open. Satisfactory outcomes have been described after reattaching the peripheral portion of the TFCC using various arthroscopic techniques [7][8][9][10]. Nevertheless, these well-known techniques are not sufficient to restore DRUJ stability when the proximal attachment is avulsed and the joint unstable.…”
Section: Introductionmentioning
confidence: 99%